Impact of acute UV-B radiation on species specific metabolic responses in poplar and willow - Yatsiv, V.; Litvinov, S.; Kutsokon, N.; Sakada, V.; Isokov, T.; Rashydov, N. (Regulatory Mechanisms in Biosystems, 2026)
Increased levels of UV-B radiation represent an important environmental factor affecting the physiology of woody plants and determining their resilience under changing climatic conditions. This study investigated the biochemical and metabolic r e sponses of microclonally propagated Populus pyramidalis × P. laurifolia cv. ‘Novoberlinska-3’ and Salix sp. cv. ‘Zhytomyrska-1’ following acute UV-B irradiation at a dose of 17 kJ/m². A broad set of metabolic parameters was assessed, including the co n tent of nucleic acids, total proteins, total lipids, total carbohydrates, a mide I and a mide II protein domains, starch, cellulose, hem i cellulose, lignin, phenylpropanoids, as well as biochemical markers of stress responses, using ATR-FTIR spectroscopy. The results revealed significant, species-specific differences in stress response pathways and dynamics. In poplar, an increase in the content of nucleic acids, lipids, starch, and aliphatic fatty acid esters was observed at an early stage, accompanied by an i n crease in the esterification index and activation of the phenylpropanoid pathway. An increase in the amide I / amide II ratio ind i cated the formation of misfolded proteins , which may represent an element of proteomic modification during stress. At a later stage, a decrease in cellulose, hemicellulose and phenylpropanoid content was observed, indicating a transition to a phase of long-term adaptation in poplar. In contrast, willow demonstrated a rapid intense response, characterised by a sharp increase in the content of lipids, carbohydrates, starch, cellulose, and hemicelluloses, accompanied by a decrease in the amide I / amide II ratio and inhibition of protein synthesis. A significant increase in the content and proportion of phenylpropanoids indicated intense activation of secondary metabolism a s well as the induction of a potent antioxidant response. Therefore, willow implements a model of rapid resource mobilisation, whereas poplar employs a slower, more structurally oriented adaptation strategy. The o b tained data demonstrate the high species-specificity of response mechanisms to UV-B radiation stress in Salicaceae tree species and highlight the potential of using a combination of spectroscopic methods to characterise clones based on their resistance to abiotic stress.